Health Education Innovation: Understanding the Role of Counseling via Video Media in Implementing Electronic Medical Records in Hospitals - Eko Prihati; Septo Pawelas Arso; Farid Agushybana; Taufik Muhtarom (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Electronic medical records (EMR) have made the management of patient health information more efficient by replacing manual record keeping. However, health workers still need to understand and apply RME well to get the maximum benefits. The role of counseling is needed for health workers in changing the use of manual media to digital. The research method uses scoping review. Based on the PubMed database as many as 88,041 articles with the keyword "electronic medical records" and as many as 84 articles with the search keyword "electronic medical records and video learning". The results of article screening in the last 10 years from 2013 – 2023 were 74 articles. Then there are exceptions based on article type, namely Clinical Trial as many as 2 articles and Randomized Controlled Trial as many as 1 article. So that articles that match the theme: review and systematic review as many as 10 articles. VOSviewer generates network, overlay and density visualization. The role of counseling through video media in electronic medical records is very important. The counseling provided does not help them deal with social, emotional, and psychological problems that may arise as a result of such changes. Keywords: scooping review, literature review, healthcare professional, VOSviewer, technology